Pengaruh Motivasi Kerja Dan Komitmen Organisasi Terhadap Kinerja Pegawai Pada Balai Prasaranan Permukiman Wilayah Sulawesi Barat - Halim, Agus; Fajariani, Nur; Ramadhan, Adam (LPPM Universitas Muhammadiyah Mamuju, 2024)
This study aims to determine the effect of work motivation and organizational commitment variables on employee performance at the West Sulawesi Regional Settlement Infrastructure Center. The research method used is by using quantitative methods with primary data using a questionnaire. Respondents in the study were all employees who worked at the West Sulawesi Provincial Settlement Infrastructure Center, the samples used were technical Nonprobability Sampling with a total sample of 36 respondents. The formula in this study uses multiple linear regression, validity test, reliability test, multiple linear regression, t test, and f test. The results in this study indicate that work motivation and organizational commitment partially and simultaneously have a significant influence on employee performance at the West Sulawesi Regional Settlement Infrastructure Center. The contribution of work motivation and organizational commitment to employee performance at the West Sulawesi Regional Settlement Infrastructure Center is still weak with a value of 41.6%, meaning that there are still other factors of 58.4% which have an influence on employee performance at the West Sulawesi Regional Settlement Infrastructure Center.